PERAN KOMITE SEKOLAH DALAM MENINGKATKAN MUTU SARANA DAN PRASARANA PENDIDIKAN - Miranti, Miranti (CV. ADIBA AISHA AMIRA, 2024)
Committee school is self-supporting body that place role and society in order to upgrade, generalization, and efficiency of education management in set of good education at education of school progress, band of school education and also education band external school. Research Target this is the to Know role of school committee in facilities and basic facilities levying. Focus in research this is the; Role of school committee in facilities and basic facilities levying in SMAN 2 Halong. Researcher uses research method qualitative descriptive, data collecting technique as used in research this is the circumstantial interview, participant observation and documentation study. Technique of data validity uses triangulation. Result and conclusion in research this is the; Role of school committee in of vital importance levying of school facilities and basic facilities for by existence of acceptable medium then study activity can walk with maximal.